Fortællingen i fokus. Vartovbogen 1981 - Mortensen, Viggo (Grundtvig-studier, 1982)
Focus on the Narrative The Vartov Book. Edited by Asta Poulsen, Jørgen Kristensen and E. Jakob Petersen. 168 pp. Published Kirkeligt Samfunds Forlag. Reviewed by Viggo Mortensen. by This review is also largely in the form o f an informative article showing how Grundvig’s authorship is still an inspiration, not only within the traditional Grundtvig circles but also in the current debate on Church politics and cultural affairs.The editors o f The Vartov Book have elected to centre their essays on a view expressed in a theological dissertation that was presented at Århus University in 1981, in which major areas o f Grundtvig’s theology are interpreted on the basis that “ Christianity at heart is a narrative” (Sv. Bjerg: The Basic Christian Narrative, Århus 1981, cf. A . Pontoppidan Thyssen in Danish Theological Journal 1/1982).Amongst the many essays in The Vartov Book that in various ways point to the value o f narrating reality - before, that is, philosophy, politics, behavioural science and statistics had alienated us from the world - Viggo Mortensen singles out Peter Balslev-Clausen’s treatment o f Grundtvig’s poem, “ Thou faded leaves, thou cool wind” (I falmede blade, du kølige vind). This poem, now included in the supplement to the Danish Hymnbook - “46 Hymns”, is seen in an authoritative analysis as an element in Grundtvig’s wrestling with the basic conditions o f existence. In fact it is these basic conditions that are the subject o f all the essays.